2020
DOI: 10.1057/s41599-020-0419-2
|View full text |Cite
|
Sign up to set email alerts
|

Segregating socioeconomic classes leads to an unequal redistribution of wealth

Abstract: Social living groups are organised in social hierarchies often exhibiting inequalities in beings. Investigating class segregation and the use of punishment applied downward in the rank acts as a key aspect to ascertain how dominant and subordinate partners cooperate to achieve mutual profit. In human subjects coming from countries with an uneven wealth distribution, this mutual profit may be reduced, especially for the lower socioeconomic classes. We implemented an Iterated Prisoner's Dilemma Game experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…In the literature, there exist some works that use ABM, game theory, and human subject experiments. In all research cases, none used a hybrid approach; either game theory was the context of the human subject experiment while the ABM was used to generate input data [78][79][80][81] or the ABM was used to validate the result of the human subject experiment. 82,83 In this section, we provided the background to ABM and simulation, CGT with specific attention to hedonic games, and human subject experiment applications in these two contexts; this provides the background need for our research approach.…”
Section: Abmscorementioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there exist some works that use ABM, game theory, and human subject experiments. In all research cases, none used a hybrid approach; either game theory was the context of the human subject experiment while the ABM was used to generate input data [78][79][80][81] or the ABM was used to validate the result of the human subject experiment. 82,83 In this section, we provided the background to ABM and simulation, CGT with specific attention to hedonic games, and human subject experiment applications in these two contexts; this provides the background need for our research approach.…”
Section: Abmscorementioning
confidence: 99%
“…In the literature, there exist some works that use ABM, game theory, and human subject experiments. In all research cases, none used a hybrid approach; either game theory was the context of the human subject experiment while the ABM was used to generate input data 78–81 or the ABM was used to validate the result of the human subject experiment. 82,83…”
Section: Introductionmentioning
confidence: 99%
“…In an incentive situation, Dal Forno and Merlone [50] used the social dilemma to run a human subject experiment to capture human behavior, where grounded theory was used to reveal the rules from the experiment; these rules were then used as an input to the ABMS to check the accuracy of results from grounded theory. Pansini et al [51] did a human subject experiment based on the prisoners' dilemma to study how mutual profitability can be gained in a society with uneven distribution of wealth between citizens while the ABMS was used to validate the result.…”
Section: Game Theory and Agent-based Modeling In Human Subject Experimentationmentioning
confidence: 99%
“…We are aware that the individuals’ unequal resource holdings affect the willingness to cooperate at a given time ( Pansini et al, 2020 ). In view of the research results involving asymmetry, it is generally believed that asymmetry can have negative consequences for interpersonal relationships ( Molho et al, 2019 ), which means asymmetry is typically associated with more selfish behavior ( Handgraaf et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the research results involving asymmetry, it is generally believed that asymmetry can have negative consequences for interpersonal relationships ( Molho et al, 2019 ), which means asymmetry is typically associated with more selfish behavior ( Handgraaf et al, 2008 ). We are aware that the individuals’ unequal resource holdings affect the willingness to cooperate at a given time ( Hauser et al, 2019 ; Riccardo Pansini et al, 2020 ). In previous research, it was found that asymmetric settings would reduce the cooperative behavior of individuals, and they did not reach a consistent conclusion on the cooperative differences between the strong and weak individuals ( Croson, 1999 ; Beckenkamp et al, 2007 ; Phillips, 2017 ).…”
Section: Introductionmentioning
confidence: 99%